Anti-synthetase syndrome with anti-PL-7 antibody positive in a child: a case report and literature review - Liu, Jia; Nie, Nana; Zhang, Ranran; Wang, Dahai; Lin, Yi; Chang, Hong (Frontiers in Immunology, 2025)
BackgroundAnti-synthetase syndrome (ASS) is a rare autoimmune myopathy and forms part of the idiopathic inflammatory myopathies (IIMs). A distinctive feature of ASS is the presence of anti-aminoacyl tRNA synthase (ARS) antibodies, which target synthetases, leading to inflammation in muscles, lungs, and other tissues.Case presentationA case of a 12-year-old Chinese girl with recurrent fever, myalgia, and Gottron’s papules is reported. Serum creatine kinase was markedly elevated, and chest CT revealed interstitial changes. Magnetic Resonance Imaging (MRI) of the left thigh indicated soft tissue swelling and interstitial fluid accumulation. Electromyography demonstrated myogenic injury. Pathological examination of a left thigh muscle biopsy revealed local edema, focal lymphocyte infiltration, and proliferation and dilation of interstitial small vessels. The myositis antibody spectrum test was positive for anti-PL-7 antibodies. Treatment with glucocorticoids and methotrexate led to significant improvement in her condition.ConclusionThis case represents the youngest reported patient with PL-7 positive ASS to date.